Extended Postoperative Prophylactic Antibiotics with First-Generation Cephalosporin Do Not Reduce the Risk of Periprosthetic Joint Infection following Aseptic Revision Total Knee Arthroplasty - Kuo, Feng-Chih; Lin, Po-Chun; Bell, Kerri L.; Ko, Jih-Yang; Wang, Ching-Jen; Wang, Jun-Wen (The Journal of Knee Surgery, 2020)
Postoperative prophylactic antibiotics administered within 24 hours of primary total knee arthroplasty (TKA) have been documented to prevent periprosthetic joint infection (PJI). However, the effectiveness of this regimen is still unclear in aseptic revision TKA. The purpose of this study was to evaluate whether extended postoperative prophylactic antibiotics would reduce the PJI rate compared with the current 24-hour standard postoperative prophylactic antibiotics after aseptic revision TKA. A retrospective review of 236 patients (46 men, 190 women, 252 knees) who underwent aseptic revision TKA between 2005 and 2013 was conducted. Patients who underwent septic revision, had a positive intraoperative culture, or who had less than 2 years of follow-up were excluded. Patients were divided according to the duration of postoperative prophylactic antibiotics to standard group (76 knees, ≤ 24 hours) or extended group (176 knees, > 24 hours). PJI was determined by the Musculoskeletal Infection Society criteria. A multivariate Cox proportional hazards regression analysis was performed. The mean follow-up was 5.2 ± 2.5 years. Patients with extended postoperative prophylactic antibiotics had a lower PJI rate (1.1%) compared with standard group (3.9%), but the difference was not statistically significant (p = 0.14). Body mass index ≥ 30 kg/m2 was the only independent risk factor of PJI (adjusted hazard ratio [HR]: 9.59; 95% confidence interval [CI]: 1.07–86.04, p = 0.043). The use of extended postoperative prophylactic antibiotics was not a risk factor for PJI (adjusted HR: 0.34; 95% CI: 0.06–2.04, p = 0.238). After 10 years, the two groups had similar infection-free implant survival rate (95.9 vs. 98.9%, p = 0.15). Our findings demonstrate that extended postoperative prophylactic antibiotics did not reduce PJI rate compared with the standard group in aseptic revision TKA. A further prospective, randomized study with a standardized postoperative antibiotic protocol is necessary to address this topic. Level of evidence is prognostic Level III.
Keywords: Antibiotic Prophylaxis; periprosthetic joint infection; aseptic revision; total knee arthroplasty